Бесы ebook - Dostoyevsky, Fyodor (The Russian Library., 2014)
This is original Russian language text of Dostoyevsky's rich political novel Demons ( Besy in Russian). The story is a testimonial of life in Imperial Russia in the late 19th century. Dostoyevsky's life of ideas and spiritual realism concept is presented through his definition of evil as the passion for power. The demons are ideas, such as: idealism, rationalism, empiricism, materialism, utilitarianism, positivism, socialism, anarchism, nihilism and atheism. This edition is part of the Russian Library series from Sovereign Classic www.sovereignclassic.net